2015
DOI: 10.5430/ijfr.v6n3p163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of International Trade on Economic Growth in Nigeria (1988-2012)

Abstract: The study examines the impact of international trade on economic growth in Nigeria, using net export (i.e total export less total import) and Balance of Payment as proxies for international trade while Gross Domestic Product represent economic growth. The study employed regression analysis as the method of analysis using co-integration and error correction modeling techniques to find the long-run relationship between economic performance and international trade. Only Total Export (TEX) remains positive and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…In the t-test, the exchange rate variable (ln EXR) generated the t-statistic value of -4.372980 with a significant probability value of 0.0000 meaning that there is a significant negative effect between the exchange rate variable (ln EXR) on economic growth (GDP per capita). The results of this study are in accordance with the results of research from Grauwe and Schnabl (2008), Chirwa and Odhiambo (2016), Abubakar (2015), Gul et al, (2012), Barguellil et al, (2018) and Umaru et al, (2018) that the exchange rate negatively affects economic growth. One of the reasons for the increase in the exchange rate is the support for adequate export growth so that it will increase the demand for the national currency (Rudiawan and Meirinaldi, 2019).…”
Section: Effect Of Exchange Rate On Economic Growthsupporting
confidence: 92%
“…In the t-test, the exchange rate variable (ln EXR) generated the t-statistic value of -4.372980 with a significant probability value of 0.0000 meaning that there is a significant negative effect between the exchange rate variable (ln EXR) on economic growth (GDP per capita). The results of this study are in accordance with the results of research from Grauwe and Schnabl (2008), Chirwa and Odhiambo (2016), Abubakar (2015), Gul et al, (2012), Barguellil et al, (2018) and Umaru et al, (2018) that the exchange rate negatively affects economic growth. One of the reasons for the increase in the exchange rate is the support for adequate export growth so that it will increase the demand for the national currency (Rudiawan and Meirinaldi, 2019).…”
Section: Effect Of Exchange Rate On Economic Growthsupporting
confidence: 92%
“…In several studies, trade openness has been found to be an important factor affecting the economic growth of developing countries. Adeleye et al (2015) investigated the effect of trade on growth in Nigeria, using error correction modelling techniques. The study found a long-run significant positive effect of trade, whereas other explanatory variables remained insignificant, which suggests that the economy derives substantial benefits from trade openness.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…(Aboubacar, Xu, & Ousseini, 2015) focused in whether the foreign aid (AID) has an important effect on economic growth in the member countries of the West African Economic and Monetary Union (WAEMU). (Adeleye, Adeteye, & Adewuyi, 2015) studied the effect of international trade on economic growth in Nigeria.…”
Section: Brief Literature Reviewmentioning
confidence: 99%